FISH FAUNA OF PEDID’S TRIBUTARIES - Fazimah, Aziz; Radin Azreena, Radin Shahrom; Anisa Grace, Robert Galang; Jongkar, Grinang (UNIMAS Publisher, 2023)
The freshwater habitats in Malaysia are made up of both natural and man-made water bodies, for example, riverine, lacustrine (natural lakes, oxbow lakes, reservoirs, former mining pools) and palustrine (freshwater, peat swamps, rice field bodies) habitats (WWFM, 2002). In general, freshwater bodies will be one of the main water sources for domestic usage. For instance, Bungo Range in Sarawak is the important water catchment area in the upstream of the Sarawak Kiri River and Sarawak Kanan River and it serves as the main water source for the nearby locals, mainly Bidayuh community.